2019
DOI: 10.1016/j.ajodo.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Dental Monitoring 3D digital dental models using photograph and video mode

Abstract: This study aimed to test the accuracy of the 3-dimensional (3D) digital dental models generated by the Dental Monitoring (DM) smartphone application in both photograph and video modes over successive DM examinations in comparison with 3D digital dental models generated by the iTero Element intraoral scanner. Methods: Ten typodonts with setups of class I malocclusion and comparable severity of anterior crowding were used in the study. iTero Element scans along with DM examination in photograph and video modes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 23 publications
1
39
0
1
Order By: Relevance
“…Five papers evaluated the efficacy and reliability of orthodontic teleassistance in the diagnosis treatment and follow-up of patients [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five papers evaluated the efficacy and reliability of orthodontic teleassistance in the diagnosis treatment and follow-up of patients [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Morris et al [ 24 ] stated that three dimensional impressions taken with dental monitoring software do not differ greatly to those taken with an intraoral scanner (iTeroElement, Align Technology, Santa Clara, CA, USA). There was a clinically insignificant mean difference of 0.02 mm between the digital models generated with dental monitoring and intraoral scans, suggesting and therefore judging it clinically insignificant [ 24 ]. Heather et al [ 26 ] evaluated the reliability and accuracy of DM.…”
Section: Resultsmentioning
confidence: 99%
“…Common benefits mentioned by patients included better communication with the orthodontist, reduced number of office visits, and increased convenience. Morris et al [13], Moylan et al [14], and Kuriakose et al [15] have all studied and confirmed the clinical accuracy of DM in measuring and tracking tooth movement.…”
Section: Introductionmentioning
confidence: 83%
“…11 studies were considered eligible. [11][12][13][14][15][16][17][18][19][20][21] A summary of study characteristics is provided in the Table 1. The earliest study was published in 2013.…”
Section: Phasementioning
confidence: 99%